KEKELIRUAN-KEKELIRUAN DALAM MEMAHAMI KONSEP-KONSEP TEORETIS HALEY TENTANG METAFORA: SEBUAH KAJIAN METALINGUAL - Joko Kusmanto; Anni Holila Pulungan (Prasasti: Journal of Linguistics, 2022)
This paper is the result of meta-lingual research on the application of Haley's metaphor theory. The research objective is to analyze and evaluate whether Haley's metaphorical theory concept is appropriately used and applied in the research data. The research design is qualitative with analytical-descriptive, conceptual-empirical, and literature methods. The data source is in the form of six scientific articles that apply Haley's metaphorical theory and have been published in six different scientific journals in Indonesia. The research data consists of two types of data, namely (i) main data in the form of meta-lingual data and (ii) auxiliary data in the form of object language data. The results of data analysis and discussion indicate that there are conceptual errors in the application of Haley's metaphorical theory in the six data sources. Generally, these mistakes can be grouped into three categories, namely errors in understanding (i) Haley's definition of metaphor, (ii) hierarchical terms of perceptual space, and (iii) application of the hierarchical concept of Haley's perceptual space in the analysis of metaphorical expressions. The main cause of these errors is that (i) Haley's theory is not referenced directly from Haley and (ii) only one of Haley's writings is referred to. Thus, the research results in that data source eventually become questions.